SRATEGI PEMBELAJARAN GURU SMPN 42 PEKANBARUDALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Ria Angelina (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This study was conducted to describe how education is implemented at SMPN 42 Pekanbaru. The implementation of education includes strategies and obstacles faced by educators. Information and data were collected through direct observation and interviews with teachers. The research method used was descriptive qualitative. The learning strategies implemented at SMPN 42 Pekanbaru are still relevant to the independent curriculum, with the aim of keeping pace with the times. In the implementation stage of this learning model, teachers at SMPN 42 Pekanbaru have prepared several strategies for preparing students and managing the classroom. However, there are also several obstacles that hinder the implementation of these strategies in the learning process, such as obstacles from the students themselves and disturbances from outside the classroom. From this study, it can be concluded that teachers play a crucial role in the learning process in the classroom to ensure that the learning process runs effectively. Additionally, the implementation of the learning model also plays a significant role in the learning process to achieve more optimal learning outcomes.